Enhancement in t1 lipase purification recovery using the novel construct pgex4t1/his-t1 - Che Hussian, Che Haznie Ayu; Raja Abd Rahman, Raja Noor Zaliha; Leow, Adam Thean Chor; Salleh, Abu Bakar; Mohamad Ali, Mohd Shukuri; Latip, Wahhida (Informa Uk Limited, 2023)
The Geobacillus zalihae strain T1 produces a thermostable T1 lipase that could be used for industrial purposes. Previously, the GST-T1 lipase was purified through two chromatographic steps: affinity and ion exchange (IEX) but the recovery yield was only 33%. To improve the recovery yield to over 80%, the GST tag from the pGEX system was replaced with a poly-histidine at the N-terminal of the T1 lipase sequence. The novel construct of pGEX/His-T1 lipase was developed by site-directed mutagenesis, where the XbaI restriction site was introduced upstream of the GST tag, allowing the removal of tag via double digestion using XbaI and EcoRI (existing cutting site in the pGEX system). Fragment of 6 × His-T1 lipase fusion was synthesized, cloned into the pGEX4T1 system, and expressed in Escherichia coli BL21 (DE3) pLysS, resulting in lipase-specific activity at 236 U/mg. The single purification step of His-T1 lipase was successfully achieved using nickel Sepharose 6FF with an optimized concentration of 5 mM imidazole for binding, yielding the recovery of 98%, 1,353 U/mg lipase activity, and a 5.7-fold increase in purification fold. His-T1 lipase was characterized and was found to be stable at pH 5–9, active at 70 °C, and optimal at pH 9.